Analysis on Distribution and Evolution of Fiber Contact Force in the Fiber Assembly of Equal Size Fiber Under Triaxial Compression - Yong Li; Haowei Wang; Lei Li; Ridong Li; Hongzhou Zhang (Journal of Natural Fibers)
Fiber is similar to a long rod-shaped particle; the fiber assembly can be regarded as an assembly of fibrous particles (cotton, flax, and hemp). For the first time, we used PFC software to simulate fiber assembly compression. To analyze the contact force among fibers in the fiber assembly with equal-sized fibers, the fiber assembly with three different fiber arrangements was designed by the PFC software to simulate the contact force among fibers. We found that the contact force among fibers forms a three-dimensional force network in fiber assembly by point or line contact. The contact number among fibers gradually increases, and many point and line contacts connect to form a dense fiber contact force network with compression. The fiber arrangement significantly impacts its compression force, and the axial load of the fiber assembly under triaxial compression plays a dominant role; the effect of other directions is secondary. Some fiber indices, such as diameter and elastic modulus, significantly impact the pressure of fiber assembly.